2022
DOI: 10.1007/s10608-022-10334-9
|View full text |Cite
|
Sign up to set email alerts
|

Habit Reversal Training and Variants of Decoupling for Use in Body-Focused Repetitive Behaviors. A Randomized Controlled Trial

Abstract: Background Behavioral interventions hold promise in improving body-focused repetitive behaviors (BFRBs), such as hair pulling and skin picking. The effect of combining different treatment techniques is currently unknown. Methods In the framework of a randomized controlled crossover trial, 334 individuals with at least one BFRB were allocated either to a waitlist control or to three experimental conditions (1:1:1:1). Participants in the experimental conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…While results were significant for the primary outcome, effect sizes were medium for the PP and small but significant for the ITT analyses. Accordingly, new methods should be tested to augment efficacy—for example, by means of guided in-person treatment with a therapist (for results examining the superiority of guided intervention to self-help in other psychological disorders, see Lundström et al and Karyotaki et al) or a treatment combination incorporating established treatments such as HRT or decoupling in view of some evidence that combining different self-help treatments may amplify effects …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While results were significant for the primary outcome, effect sizes were medium for the PP and small but significant for the ITT analyses. Accordingly, new methods should be tested to augment efficacy—for example, by means of guided in-person treatment with a therapist (for results examining the superiority of guided intervention to self-help in other psychological disorders, see Lundström et al and Karyotaki et al) or a treatment combination incorporating established treatments such as HRT or decoupling in view of some evidence that combining different self-help treatments may amplify effects …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, habit replacement is a more dynamic technique that, unlike HRT, should be practiced in symptom-free intervals to reinforce a new routine in lieu of the BFRB (for HRT, a response that is not contingent on the urge to engage in the habit has been found to be ineffective). We conducted the present trial as a self-help study for various reasons: (1) few therapists specialize in the disorder, and therapists are often unaware of effective treatments, and (2) self-help is playing an increasing role in BFRB treatment to narrow the large treatment gap …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Cognitive behavioral therapy (CBT) and its related subtypes are the treatment of choice for BFRBs, particularly trichotillomania and skin picking disorder (SPD). 6,7 CBT involves identifying the situations, feelings, and thoughts that trigger an episode, systematically reducing the associated triggers, and replacing the pleasurable aspect of the unwanted behavior. 8 A 2023 randomized control trial demonstrated that a self-help manual describing habit-reversal training (HRT) and decoupling techniques led to a significant reduction in BFRBs behavior compared to a wait-listed control group (P<0.001).…”
Section: Psychotherapymentioning
confidence: 99%